HHO Gas Production Rate at Different Electrode Plate Configurations and NaOH and KOH Electrolyte Concentrations - Kultsum, Ummi; Mahyunani, Dewi; Anggoro, Cahyo Jawoto; Soumi, Andi Ibrahim (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2026)
HHO gas is being developed as an alternative fuel due to its efficiency and clean emissions. Water electrolysis with electrolytes and effective electrodes is one production method. This study assessed the efficacy of the HHO gas generator concerning the quantity of electrode plates and varying electrolyte concentrations, specifically NaOH and KOH. The HHO gas production rate during electrolysis exhibited variations with electrolyte concentrations of 2%, 4%, 6%, 8%, and 10%. The configurations of the electrode plates utilized comprised two, four, and six stainless-steel plates. The experimental findings indicated that the KOH electrolyte continuously surpassed NaOH, particularly at elevated concentrations, where increased electrolyte levels significantly enhanced the HHO gas production rate. Optimal conditions were achieved by employing six electrode plates with a 10% potassium hydroxide solution, equivalent to 66.67 grams per 600 milliliters of distilled water, yielding a maximum gas generation rate of 6.9 ml/s. Moreover, hydrostatic pressure study indicated that elevated electrolyte concentration and an increased number of electrode plates directly correlated with enhanced gas production and pressure.